A general strategy to construct uniform carbon-coated spinel LiMn2O4 nanowires for ultrafast rechargeable lithium-ion batteries with a long cycle life. Issue 31 (16th July 2015) - Sun, Weiwei; Liu, Huiqin; Liu, Yumin; Bai, Gongxun; Liu, Wei; Guo, Shishang; Zhao, Xing-Zhong
Abstract : In this paper, we propose a general strategy to construct well-defined LiMn2 O4 nanowires terminated with amorphous carbon at the edges by an ingenious method without using any template. Abstract : Control over one-dimensional growth of spinel-type LiMn2 O4 nanowires is challenging in the area of materials science due to their cubic crystal structure. The current strategy is to use a self-support template to fabricate LiMn2 O4 nanowires, which is time-consuming and limits their large-scale commercial production. In this paper, we propose a general strategy to construct well-defined LiMn2 O4 nanowires terminated with amorphous carbon at the edges by an ingenious method without using any template. Benefited from its unique carbon-coated nanowire structure, the electrode exhibits a capacitor-like rate performance and battery-like high capacity for long-time cycling. Even after 1500 cycles at an extremely high current density of 30 C, approximately 82% of its initial capacity can still be retained. Significantly, the strategy reported here will be beneficial and revelatory to manufacture other extensive one-dimensional robust carbon-decorated nanowires, paving new ways for future developments of ultrafast rechargeable lithium-ion batteries.